Pluralisme dan Kerukunan Umat Beragama di Kabupaten Alor Nusa Tenggara Timur Perspektif Maqashid Al-Ummah - Husnul Qodim; Rizal Darwis (LPPM IAIN Sultan Amai Gorontalo, 2022)
Harmony in a society is the urgency and desire of every human being. especially in religious pluralism in Indonesian society. In this plurality, the potential for conflict may occur. This study aims to analyze pluralism and religious harmony in Alor Regency, East Nusa Tenggara. This type of research is literature with primary data sources coming from books, articles, and studies related to pluralism, religion, and community harmony, especially those related to the people of the Alor Regency. The data collected was processed and analyzed by qualitative description. The results show that the people of Alor Regency always maintain harmony against the differences that live in society. Appreciation for the local wisdom of the Alor people also plays an important role. On the other hand, the role of the local government is an important pillar that can guard pluralism and the creation of harmony between religious people of different beliefs. The dialogue and collaboration between the government and the people of Alor have had a positive impact. The existence of tolerance among religious believers that has been carried out by the Alor community is a form of benefit for the people (maqashid al-ummah) in the context of Islamic law.